The Passenger Satisfaction Analysis of Commuter Line Facility: A Case of Manggarai Station, Indonesia - Betty Rosyana Manurung; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
Manggarai Station is one of the railway stations offering rail-based land transportation services managed by PT KAI Commuter, a subsidiary of PT KAI Indonesia. Aiming for completion in 2025, Manggarai Station is currently undergoing repairs at multiple facilities. Multiple facilities are offered to meet consumer needs. The presence of this train will arouse people's interest in rail travel. The services provided by Manggarai Station are one aspect to consider. To know how Manggarai Station's facilities and services support customer satisfaction. The research method used in this study is a descriptive analysis method using primary data obtained directly by the researchers from the results of data collection using questionnaires. The purpose of this study is to analyze how high the services and facilities offered by Manggarai station are. Consumer satisfaction influences the subconscious response to always use trains over other modes of transport. It has long-term effects and also affects the profits generated. Based on the above case, the researcher is interested in conducting a study entitled analysis of his KRL commuter facilities on passenger satisfaction at Manggarai station.